(untitled) (Itinera, 2014)
If you analyze Tim Burton’s filmography, the relationship between his entire work and the philosophical sublime could appear clear. First of all the use of darkness as the symbol of your inner being and also the concept of expressionism seen as the union between dark and light, shadows and brightness, the double nature of the sublime. Moreover, women in Tim Burton’s movies are savior angels, and the sublime is seen as the elevation of the soul, which is the thought we can find in Immanuel Kant, Baldine Saint Girons or Edmund Burke’s works. Another important element is Danny Elfamn´s music, which is played in all Tim Burton´s movies, which is able to magnify the idea of the sublime in all his works.